Mengukur Peran Kualitas Pelayanan, Premi, Dan Promosi Terhadap Keputusan Pembelian Produk Asuransi - Mappamiring Mappamiring; Muhammad Tafsir (STIE AMKOP, 2023)
The aim of this research is to examine the role of service quality, premiums and promotions on insurance product purchasing decisions. This research was conducted at the insurance company PT. Askrindo (Persero) Makassar Branch. The background for choosing a research topic is because competition in the insurance industry is very tight and the main products offered are services so that service quality, premiums and promotions are some of the most important things that influence the success of winning the market. In this study, researchers found different results from the two independent variables to the dependent variable. To test the data obtained, several analytical methods were used, such as validity, reliability, normality, multicollinearity, heteroscedasticity, regression test, partial test and determination test. Based on the research results, the researchers drew the following conclusions: Based on the test results, service quality has a positive and insignificant effect on purchasing decisions. In the second test, the premium has a positive and significant effect on purchasing decisions. In the third test, promotions had a positive and significant effect on purchasing decisions. Keywords: Quality of service, premiums, promotions, insurance